Exponential Lower Bound for Berge-Ramsey Problems - Pálvölgyi, Dömötör (Graphs and combinatorics, 2021)
We give an exponential lower bound for the smallest $$N$$ N such that no matter how we c -color the edges of a complete $$r$$ r -uniform hypergraph on $$N$$ N vertices, we can always find a monochromatic Berge- $$K_n$$ K n .